Enhanced strength and reduced elastic modulus of biomedical metastable β Ti–Nb alloy via intermediate phase transformation - Meng Qiang; Xi-rong Yang; Geng-jie Wang; Xiao-yan Liu; Lei Luo; Qun Ren; Jing-zhong Wang (Materials & Design)
The high strength of biomedical titanium alloys is primarily attained through precipitation strengthening of the α phase. However, the plasticity and elastic modulus of these alloys are often limited due to their inherent strength–toughness tradeoff and the high-modulus α phase. Metastable β-type Ti–Nb alloys were subjected to equal-channel angular pressing (ECAP) deformation and aging treatment in this study. The lattice defects and high distortion induced by the deformation can provide nucleation sites and drive the precipitation during aging, as well as hinder the dissolution of the low-modulus stress-induced martensitic (SIM) α′′ phase introduced during the deformation, which results in the formation of fine and dispersed nanosized intermediate phases (α + ω + α′′) after short-term aging. As a result, a Ti–Nb alloy with a high strength (∼1021 MPa), low elastic modulus (∼59 GPa), and good elongation (∼12 %) is obtained. Furthermore, the competition between the ω and α phases is observed. The comprehensive mechanical properties of the alloy prepared by ECAP deformation combined with aging treatment in this study surpasses those of many reported titanium alloys prepared by traditional deformation or thermal treatment, which provides a valuable reference for the production of advanced biomedical titanium alloys.